Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/bcp.12655
|View full text |Cite
|
Sign up to set email alerts
|

The renal protective effect of angiotensin receptor blockers depends on intra‐individual response variation in multiple risk markers

Abstract: Aims Angiotensin receptor blockers (ARBs) are renoprotective and targeted to blood pressure. However, ARBs have multiple other (off‐target) effects which may affect renal outcome. It is unknown whether on‐target and off‐target effects are congruent within individuals. If not, this variation in short term effects may have important implications for the prediction of individual long term renal outcomes. Our aim was to assess intra‐individual variability in multiple parameters in response to ARBs in type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 38 publications
0
44
0
1
Order By: Relevance
“…The finding that the albuminuria‐lowering effect of dapagliflozin was independent of changes in HbA1c or SBP suggests a dissociation of the albuminuria response from responses in HbA1c or SBP. This uncoupling of responses in multiple characteristics of a single drug has also been observed with other drugs including ACE inhibitors, ARBs, dipeptidyl peptidase‐4 inhibitors and endothelin receptor antagonists . The underlying mechanisms of this uncoupling in response are unknown and require further study.…”
Section: Discussionmentioning
confidence: 75%
“…The finding that the albuminuria‐lowering effect of dapagliflozin was independent of changes in HbA1c or SBP suggests a dissociation of the albuminuria response from responses in HbA1c or SBP. This uncoupling of responses in multiple characteristics of a single drug has also been observed with other drugs including ACE inhibitors, ARBs, dipeptidyl peptidase‐4 inhibitors and endothelin receptor antagonists . The underlying mechanisms of this uncoupling in response are unknown and require further study.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, the ARBs significantly changed seven out of 11 measured renal risk markers. Integrating all risk markers in a score showed that it provided a better prediction of the drug effect on hard renal outcomes than any change in single markers [42,43]. External validation studies confirmed these results [44].…”
Section: Integrating Multiple Renal Risk Markersmentioning
confidence: 79%
“…Clinical trials in patients with DKD focus on response in the overall population but do not take into account how patients respond to the drug individually. Careful subgroup analyses of recent trials in DKD, albeit post‐hoc, suggested that disease molecular pathology differed between subgroups and disease subgroups associated with response, such that a subgroup of patients benefitted whereas other subgroups did not or were even harmed . The failure of almost all trials in the last decade indicates that this one‐size fits all approach is inadequate.…”
Section: The Use Of Systems Biology Approach To Predict Patients' Resmentioning
confidence: 99%